Continuous GNSS raw data measured from POLARSTERN deck during the MOSAiC expedition with POLARSTERN to the Arctic on 2020-10-08 - Friederike Fohlmeister; Lothar Kurz; Martin Kriegel; Gunnar Spreen; Antonia Immerz (PANGAEA, 2023)
Raw data acquired by a JAVAD Delta 3 GNSS Receiver with a resolution of 50Hz on board RV Polarstern during the MOSAiC expedition. The data is stored in JAVAD extquotesingles .jps format (JAVAD GNSS, GREIS – GNSS Receiver External Interface Specification, San Jose, USA, 2022 (download available at https://www.javad.com/jgnss/support/manuals.html)). Each file contains data of one day with a typical file size of 1GB. The receiver was equipped with a multi-frequency GNSS antenna which was mounted on the ship extquotesingles observation deck. It has to be noted that the main mast and the ship extquotesingles chimney lead to a shadowing of GNSS observation links in at least two directions seen from the antenna position. The data was collected for measuring scintillation activitiy in the central arctic. Processed scintillation measurements with a 1 minute resolution are available (doi:10.1594/PANGAEA.956019).
In: Fohlmeister, F et al. (2023): Continuous GNSS raw data measured from POLARSTERN deck during the MOSAiC expedition with POLARSTERN to the Arctic [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.956114